Influence of oat seed extract bioflavonoids on the antioxidant status of geese - Danchenko, Olena; Данченко, Олена Олександрівна; Данченко, Елена Александровна; Zdorovtseva, Liubov; Здоровцева, Любов Миколаївна; Здоровцева, Любовь Николаевна; Danchenko, Mykola; Данченко, Микола Миколайович; Данченко, Николай Николаевич; Yakoviichuk, О.; Sukharenko, Olena; Сухаренко, Олена Іванівна; et al. (My University, 2019)
The peculiarities of the effect of bioflavonoids extract of oat seedlings on the state of prooxidant-antioxidant equilibrium in liver tissues of geese in the pre-slaughter period was clarified. It has been proved that oat extract stabilizes this equilibrium throughout the research period, and during the physiological stress of the formation of juvenile feathers, it promotes activation of the antioxidant system of the liver of geese. The results of the correlation and cluster analysis show that the activation of the antioxidant defense system is the result of the inclusion of alternative mechanisms that are characterized by a 25.0% lower level of consistency of the components of the antioxidant defense system. The increase in the average weight of the 63-day geese of the experimental group by almost 20.0% compared with control is an additional confirmation of the increase of the antioxidant status of geese under the influence of oats extract
Keywords: geese; liver; antioxidant system; oat seed extract; correlation; cluster analysis